Zomo the rabbit : a trickster tale from West Africa - McDermott, Gerald (New York : Scholastic, 1992)
The fleet-footed Zomo outwits his larger foes with guide and trickery. And like his African cousins Spider and Tortoise, he uses his wits to gain wisdom.
Keywords: Rabbits -- Fiction; Folktale -- African